Acne-induced Post-inflammatory Hyperpigmentation: From Grading to Treatment - Nicole Auffret; Marie-Thérèse Leccia; Fabienne Ballanger; Jean Paul Claudel; Serge Dahan; Brigitte Dréno (Acta Dermato-Venereologica)
Acne-induced post-inflammatory hyperpigmentation (AI-PIH) can occur without any visible clinical evidence of significant inflammation, even in patients with mild to moderate acne. Currently, visual assessment is the main criterion for evaluating the severity of PIH, including that of AI-PIH in daily clinical practice. Treatment indications are lacking. This work provides an easy-to-use AI-PIH severity grading tool for daily clinical practice as well as indications on how to prevent and treat AI-PIH using currently available treatment options. Five experts in acne provided a short overview concerning the epidemiology and physiopathology of AI-PIH, developed an AI-PIH severity grading tool, and proposed preventive measures as well as an AI-PIH treatment algorithm. Only a small number of epidemiological data on AI-PIH are available, confirming that the condition is mainly observed in patients with Phototypes IV to VI. The physiopathology of AI-PIH is still not completely understood. Innate immunity, Cutibacterium acnes, and external factors such as UV radiation, visible light, and air pollution play a role in its development. An easy-to-use AI-PIH severity grading tool (Acne PIgmentation Grading) allows quick assessment of acne severity during the consultation, and, in addition to proposed preventive measures, a treatment algorithm is proposed according to AI-PH severity. Patient education remains key. Providing an AI-PIH severity assessment tool as well as preventive and treatment recommendations may help to manage AI-PIH more efficiently.